2023
DOI: 10.1097/hep.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant gemcitabine plus cisplatin versus capecitabine in node-positive extrahepatic cholangiocarcinoma: the STAMP randomized trial

Abstract: Background and Aims: The effectiveness of gemcitabine-based adjuvant chemotherapy is unclear in cholangiocarcinoma. We investigated the role of adjuvant gemcitabine plus cisplatin (GemCis) in a homogeneous group of high-risk patients with resected, lymph node-positive extrahepatic cholangiocarcinoma. Approach and Results: Adenocarcinoma of perihilar or distal bile duct with regional lymph node metastasis who underwent curative-intent surgery (R0/ R1) was eligible. Patients were randomized to receive GemCis (ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Our data suggest that AC may not provide an OS benefit over surgery alone in older adults. If older adults are offered AC, then single-agent chemotherapy should be the preferred option and would be in line with the standard of care, especially as suggested by the phase II STAMP study that the AC combination of gemcitabine and cisplatin may not improve survival compared with single-agent capecitabine for resected ECC . The ACTICCA-1 (Adjuvant Chemotherapy With Gemcitabine and Cisplatin Compared to Standard of Care After Curative Intent Resection of Biliary Tract Cancer) study (NCT02170090), a large phase III trial, is also evaluating the role of gemcitabine and cisplatin compared with capecitabine in the adjuvant setting for BTC.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that AC may not provide an OS benefit over surgery alone in older adults. If older adults are offered AC, then single-agent chemotherapy should be the preferred option and would be in line with the standard of care, especially as suggested by the phase II STAMP study that the AC combination of gemcitabine and cisplatin may not improve survival compared with single-agent capecitabine for resected ECC . The ACTICCA-1 (Adjuvant Chemotherapy With Gemcitabine and Cisplatin Compared to Standard of Care After Curative Intent Resection of Biliary Tract Cancer) study (NCT02170090), a large phase III trial, is also evaluating the role of gemcitabine and cisplatin compared with capecitabine in the adjuvant setting for BTC.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the comments provided by Ya Fei Hu and colleagues regarding the STAMP trial. [1] Our study demonstrated that, for patients with resected extrahepatic cholangiocarcinoma (CCA) with lymph node metastases, adjuvant gemcitabine plus cisplatin did not result in significant improvements in survival outcomes compared with adjuvant capecitabine (CAP). In terms of the clinical implication of adjuvant gemcitabine plus cisplatin in comparison with CAP for patients with overall biliary tract cancer, we are awaiting the results of the ongoing ACTICA-1 trial.…”
mentioning
confidence: 80%
“…We appreciate the comments provided by Ya Fei Hu and colleagues regarding the STAMP trial 1 . Our study demonstrated that, for patients with resected extrahepatic cholangiocarcinoma (CCA) with lymph node metastases, adjuvant gemcitabine plus cisplatin did not result in significant improvements in survival outcomes compared with adjuvant capecitabine (CAP).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…To the editor, We read with great interest the article by Hyehyun et al [1] The authors report that adjuvant gemcitabine plus cisplatin (GemCis) did not improve survival outcomes compared with capecitabine for resected lymph-node-positive extrahepatic cholangiocarcinoma and suggest that adjuvant capecitabine should remain the standard of care for these patients.…”
mentioning
confidence: 99%